Penggalian Gunung Kapur sebagai Destinasi Wisata dalam Perspektif Fiqh Bi’ah: Studi di Desa Jaddih Kecamatan Socah Bangkalan Madura - Sarkawi, Sarkawi; Qadariyah, Lailatul; Karim, Busro (Bukhori: Kajian Ekonomi dan Keuangan Islam, 2024)
Purpose: The purpose of this research is to determine the view of fiqh bi'ah on the excavation of the High Hill in Jaddih village. Method: This study uses a qualitative method that extracts data using interviews and documentation. Results: The results of this study indicate that the excavation of the limestone hill in Jaddih village is not in line with the basic principles of environmental preservation in the study of Fiqh bi'ah. The damage and pollution caused by the excavation of this limestone hill include damage to roads, changes in air quality, changes in landscape roads, changes in air quality, landscape changes, and several other negative impacts. Limitation: All these negative impacts are indeed small in scale, considering that the excavation of this limestone hill is included in the classification of class C excavation mining activities and does not have a significant impact on the sustainability of the area. However, continuous excavation remains a concern for many parties to anticipate things. be a concern for many parties to anticipate undesirable things, especially to preserve this nature. The preservation of this nature is fardhu kifayah. Contribution: The results of this study will make a scientific contribute to similar studies and enrich the intellectual treasures of digging mountains or hills that are commonly performed in Madura.